2015
DOI: 10.1038/bmt.2014.302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes at two institutions of patients with ALL receiving ex vivo T-cell-depleted or unmodified allografts

Abstract: We compared outcomes of adult patients receiving T-cell depleted (TCD) hematopoietic stem cell transplantation (HCT) without additional GVHD prophylaxis at Memorial Sloan Kettering Cancer Center (MSKCC, N=52) with patients receiving conventional grafts at MD Anderson Cancer Center (MDACC, N=115) for acute lymphoblastic leukemia in CR1 or CR2. Patients received myeloablative conditioning. Thirty-nine patients received ATG at MSKCC and 29 at MDACC. Cumulative incidence of grades 2-4 acute (p=0.001, 17.3% vs. 42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…Additionally, the lack of a control group of patients receiving unmodified grafts during the same period, precludes the comparisons of the results of this approach with a more widely used approach with unmodified grafts. Notwithstanding, other studies with a control group have also shown a low incidence of GVHD without an increase in disease relapse when compared with unmodified graft recipients 27,41,42 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, the lack of a control group of patients receiving unmodified grafts during the same period, precludes the comparisons of the results of this approach with a more widely used approach with unmodified grafts. Notwithstanding, other studies with a control group have also shown a low incidence of GVHD without an increase in disease relapse when compared with unmodified graft recipients 27,41,42 .…”
Section: Discussionmentioning
confidence: 91%
“…Management of early toxicities, engraftment, and infections was performed according to standard clinical practice as previously described 2527 .…”
Section: Methodsmentioning
confidence: 99%
“…[15,29] Positive selection of CD34+ cells was performed by using Isolex 300i Magnetic Cell Separator (Baxter, Deerfield, IL) and subsequent sheep RBC rosette depletion,[13] or using the CliniMACS CD34 Reagent System (Miltenyi Biotech, Gladbach, Germany). [21,30] In addition, 32 patients received combined T cell depleted BM and PBSC allografts, on a protocol in which both products were being administered. Equine anti-thymocyte globulin (ATG, 15 mg/kg/dose × 2 equine) or rabbit ATG (2.5 mg/kg/dose × 2) provided graft rejection prophylaxis.…”
Section: Methodsmentioning
confidence: 99%
“…(1, 2, 20) Positive selection of CD34+ cells was performed by using Isolex 300i Magnetic Cell Separator (Baxter, Deerfield, IL) and subsequent sheep RBC rosette depletion,(2) or using the CliniMACS CD34 Reagent System (Miltenyi Biotech, Gladbach, Germany). (8, 21) Equine or rabbit anti-thymocyte globulin (ATG) was used to promote engraftment in the majority of cases. Patients did not receive any other post-transplant immunosuppressive prophylaxis.…”
Section: Methodsmentioning
confidence: 99%